Eddy‐Induced Transport and Kinetic Energy Budget in the Arabian Sea. Issue 23 (1st December 2020) - Zhan, Peng; Guo, Daquan; Hoteit, Ibrahim
Abstract: This study investigates the vertical eddy structure, eddy‐induced transport, and eddy kinetic energy (EKE) budget in the Arabian Sea (AS) using an eddy‐resolving reanalysis product. The EKE intensifies during summer in the western AS. Anticyclonic eddies (AEs) and cyclonic eddies (CEs) present warm‐fresh and cold‐salty cores, respectively, with interleaved salinity structures. The eddy‐induced swirl transport is larger in the western AS and tends to compensate for heat transport by the mean flow. Zonal drift transport by AEs and CEs offset each other, and meridional transport is generally weaker. Eddies also produce notable upward heat flux during summer in the western AS, where ageostrophic circulations are induced to maintain a turbulent thermal wind balance. Plausible mechanisms for EKE production are governed by baroclinic and barotropic instabilities, which are enhanced in summer in the western basin, where signals are quantitatively one order larger than the turbulent wind inputs. Key Points: Eddy activities and eddy‐induced transport play a crucial role in maintaining oceanic heat and salt conditions in the Arabian Sea The western Arabian Sea is identified as a new hot spot in the global ocean with noticeable upward eddy‐induced heat transport Baroclinic and barotropic instabilities are the primary sources of eddy kinetic energy in the Arabian Sea